Evaluación de la Thdi y Thdv en transformadores de distribución monofásicos. - Mendoza Aguirre, Temístocles Valdemar (2019)
The THDI (total harmonic distortion of current) and THDV (total harmonic voltage distortion) are harmonics that are presented by the insertion of non-linear loads, such as induction cookers, ovens, among others, in an installation or electrical distribution network. The presence of harmonics generates innumerable problems that affect the power quality of the electricity supply network. These non-sinusoidal loads generate losses, heating of conductors, decrease of the power factor and in the transformer degradation of the insulation, loss in the power supply, causing an increase of the operative costs and reduction of the useful life of the elements that make up the system. In this developed research THDI and THDV are evaluated in single-phase transformers of 10, 15, 25 and 37.5 kVA that supply energy to residential consumers in the province of Loja, using a database of measurements made over a period of 3 years (2013, 2014, 2015), with the objective of obtaining characteristic curves to observe the characteristic behavior of THDI and THDV in transformers that feed residential loads with and without induction cooker. After processing the database, statistical techniques were used to determine if the database complies with a normal distribution. Finally, characteristic curves of the THDI and THDV were obtained, where the time behavior of these two parameters can be appreciated.